Mice with early retinal degeneration show differences in neuropeptide expression in the suprachiasmatic nucleus - Ruggiero, Linda (BioMed Central, 2010)
BACKGROUND: In mammals, the brain clock responsible for generating circadian rhythms is located in the suprachiasmatic nucleus (SCN) of the hypothalamus. Light entrainment of the clock occurs through intrinsically photosensitive retinal ganglion cells (ipRGCs) whose axons project to the SCN via the retinohypothalamic tract. Although ipRGCs are sufficient for photoentrainment, rod and cone photoreceptors also contribute. Adult CBA/J mice, which exhibit loss of rod and cone photoreceptors during early postnatal development, have greater numbers of ipRGCs compared to CBA/N control mice. A greater number of photosensitive cells might argue for enhanced light responses, however, these mice exhibit attenuated phase shifting behaviors. To reconcile these findings, we looked for potential differences in SCN neurons of CBA/J mice that might underly the altered circadian behaviors. We hypothesized that CBA/J mice have differences in the expression of neuropeptides in the SCN, where ipRGCs synapse. The neuropeptides vasoactive intestinal peptide (VIP) and vasopressin (VP) are expressed by many SCN neurons and play an important role in the generation of circadian rhythms and photic entrainment. METHODS: Using immunohistochemistry, we looked for differences in the expression of VIP and VP in the SCN of CBA/J mice, and using a light-induced FOS assay, we also examined the degree of retinal innervation of the SCN by ipRGCs. RESULTS: Our data demonstrate greater numbers of VIP-and VP-positive cells in the SCN of CBA/J mice and a greater degree of light-induced FOS expression. CONCLUSIONS: These results implicate changes in neuropeptide expression in the SCN which may underlie the altered circadian responses to light in these animals.